(untitled) (Journal of Universal Science Research, 2023)
Reduce, reuse, recycle is one of the key directions in the development of science and technology at this time. However, it is not enough to create opportunities for reusing PET containers. It is necessary to create mechanisms that will motivate people to collect and hand over such containers. In this article, we propose the creation of a reverse vending machine, which will issue a monetary reward to a person for handing over PET containers.